Penyimpanan Arsip Dinamis Aktif di Bagian Tata Usaha SMA Pertiwi 1 Kota Padang - Azizah, Mardiah; Rahmah, Elva (Ilmu Informasi Perpustakaan dan Kearsipan, 2012)
The purposes of the study were to (1) tell the procedure of the storage active dynamic archive at the administration office in Pertiwi 1 Senior High School Padang, (2) the problems that occurred by the administration by using storage active dynamic archive in Pertiwi 1 Senior High School Padang. Tha data was collected by doing observation and by interviewing the administration staff in Pertiwi 1 Senior High School Padang. Based on the data analysis, it can be concluded that: first, the procedure of the storage active dynamic archive in the administration office in Pertiwi 1 Senior High School Padang does not use index it spends much time to find the archieve. Second, the problems are (1) the placement of human resources does not effective, (2) lack of instruments that are needed to save the archive, (3) the space for the storage is narrow and limited that makes the archives pile up. Keywords: archive storage; active dynamic archive